Interspecific features of copper accumulation and variability in the skeletal muscle of farm animals - O. A. Zayko; T. V. Konovalova; O. S. Korotkevich; V. L. Petukhov; O. I. Sebezhko; E. E. Glushchenko; О. А. Зайко; Т. В. Коновалова; О. С. Короткевич; В. Л. Петухов; О. И. Себежко; Е. Е. Глущенко (Publishing Centre “Zolotoy Kolos” of Novosibirsk State Agrarian University, 2024)
The results of a study of copper levels in the skeletal muscles of cattle, sheep, pigs and yaks, carried out on clinically healthy animals raised in the Siberian region, are presented. The living conditions of the animals corresponded to the standard ones depending on the species. Elemental analysis of muscle tissue samples was performed using inductively coupled plasma atomic emission spectral analysis. Data processing was done using Microsoft Office Excel and the R programming language in the data analysis environment RStudio version 2023.03.1 (RStudio, PBC). In most cases, the distribution did not correspond to normal, and the variances were not homogeneous. Based on the average value and median, a descending ranked series of copper content in tissue was established: cattle < yaks < sheep < pigs, in numerical terms based on the median: 1.57: 1.29: 1.02: 1.0. The medians for copper in cattle, yaks, sheep and pigs were 1.40; 1.15; 0.024; 0.91; 0.89 mg/kg, respectively, reference intervals are 0.40–2.13, 0.30–2.16, 0.39–1.43 and 0.28–1.47 mg/kg. The most significant range of variability,based on the standard deviation and the ratio of extreme variants, is characteristic of cattle. Based on the Kruskal-Walli’s test, muscle copper accumulation differed significantly between species (H = 18.277, df = 3, p < 0.001). Pairwise comparison showed significant differences in the pairs “cattle – pigs”, “cattle – sheep” and “pigs – yaks”. Two clusters were identified based on the similarity of copper accumulation: cattle - yaks and sheep - pigs. The results can serve as an approximate physiological norm for the concentration of copper in the skeletal muscles of animals of different species and confirm the genotype’s influence on the organism’s cumulative abilities. Приведены результаты исследования уровня меди в скелетной мускулатуре крупного рогатого скота, овец, свиней и яков, которое проведено на клинически здоровых животных, выращенных в сибирском регионе. Условия содержания животных соответствовали ...